2020
DOI: 10.21203/rs.3.rs-20850/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

D-dimer as a biomarker for disease severity and mortality in COVID-19 patients: a case control study

Abstract: Background: Over 240000 cases of coronavirus disease-19 (COVID-19) has been reported since Dec. 2019. We aim to assess the use of D-dimer as a biomarker for disease severity and clinical outcome in COVID-19 patients.Methods: We retrospectively analyzed the clinical, laboratory, and radiological characteristics of 248 consecutive cases of COVID-19 in Renmin Hospital of Wuhan University, Wuhan, China from Jan 28 to Mar 08, 2020. Correlations of D-dimer upon admission with clinical staging, radiological staging, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
134
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(155 citation statements)
references
References 16 publications
(23 reference statements)
16
134
4
1
Order By: Relevance
“…Our study found higher peak d-dimer levels in patients with thromboembolic complications compared to patients with none. Elevated d-dimer level is very frequently observed in Covid associated coagulopathy and higher levels correlate with more severe disease and in-hospital mortality 40 . Tang et al reported higher d-dimer levels in non survivors compared to survivors and that anticoagulant treatment is associated with decreased mortality 41 , 42 We did observe a high failure rate of DVT prophylaxis therapy and therapeutic anticoagulation in our patients with thromboembolism.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study found higher peak d-dimer levels in patients with thromboembolic complications compared to patients with none. Elevated d-dimer level is very frequently observed in Covid associated coagulopathy and higher levels correlate with more severe disease and in-hospital mortality 40 . Tang et al reported higher d-dimer levels in non survivors compared to survivors and that anticoagulant treatment is associated with decreased mortality 41 , 42 We did observe a high failure rate of DVT prophylaxis therapy and therapeutic anticoagulation in our patients with thromboembolism.…”
Section: Discussioncontrasting
confidence: 99%
“…Although Yao et al did not specifically study the correlation between various D-dimer levels and VTE, they showed that D-dimer at a cut-off value of 0.5 µg/mL was present in more than 70% of patients with COVID-19, and an increase in D-dimer levels correlated significantly with disease severity [ 28 ]. As many COVID-19 patients may present with high levels of D-dimer due to inflammation, it is difficult to rule out VTE based on D-dimer alone in patients with high pretest probability [ 29 ].…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…This is the case for other BBs, such as D-dimer, fibrinogen, and troponin, in COVID-19 patients. [318][319][320][321][322][323] Troponin elevation has been shown to also specifically identify COVID-19 patients who develop cardiovascular complications, 323 supporting the need to determine whether elevated neuronal BBs could also be an early indicator in those patients who are developing neurovascular complications such as stroke and microvascular damage. Serial assessments of BBs could be important to identify early and continuing biomarker elevations that could trigger more frequent neurochecks in hospitalized patients and potentially establish who will benefit from neurocognitive rehabilitation in hospital settings.…”
Section: Acute Diagnosis and Triagementioning
confidence: 99%